Enhanced Refrigeration Capacity of Rare-Earth-Free Ni-Co-Mn-In-Si Heusler Alloys for Magnetic Refrigerants. (14th September 2021) - Venkatesan, Shaleni; Abhinav, E. Meher; Kavita, S.; Kumar, N. Pavan; Raja, M. Manivel; Sivaprahasam, D.; Perumal, Suresh
Abstract : NiMn-based Heusler alloy-based solid-state refrigeration technology has received great attention in the field of magnetic refrigeration due to their low energy consumption, environmental friendliness, high magnetization difference (ΔM), low thermal hysteresis (ΔThys ) across the magneto-structural transformation, and giant magnetocaloric properties at the low magnetic field. We report the promising rare-earth-free magnetic refrigerant material of Ni45 Co5 Mn37 In12 Si1 prepared by arc melting followed by heat-treatment with an inverse magnetocaloric effect and notable inverse ΔSM of 8.6 J kg −1 K −1 around 241 K. Moreover, the large refrigeration capacity (RC) of 462 J kg −1 with a wide operating temperature of ∼53.8 K is obtained for sample thus annealed for 10 h, which is relatively comparable with rare-earth-based high-performance Gd5 Si2 Ge2 materials.